The PML-associated protein DEK regulates the balance of H3.3 loading on chromatin and is important for telomere integrity - Ivanauskiene, Kristina; Delbarre, Erwan; McGhie, James D.; Küntziger, Thomas; Wong, Lee H.; Collas, Philippe (Genome Research, 2014)
Histone variant H3.3 is deposited in chromatin at active sites, telomeres, and pericentric heterochromatin by distinct chaperones, but the mechanisms of regulation and coordination of chaperone-mediated H3.3 loading remain largely unknown. We show here that the chromatin-associated oncoprotein DEK regulates differential HIRA- and DAAX/ATRX-dependent distribution of H3.3 on chromosomes in somatic cells and embryonic stem cells. Live cell imaging studies show that nonnucleosomal H3.3 normally destined to PML nuclear bodies is re-routed to chromatin after depletion of DEK. This results in HIRA-dependent widespread chromatin deposition of H3.3 and H3.3 incorporation in the foci of heterochromatin in a process requiring the DAXX/ATRX complex. In embryonic stem cells, loss of DEK leads to displacement of PML bodies and ATRX from telomeres, redistribution of H3.3 from telomeres to chromosome arms and pericentric heterochromatin, induction of a fragile telomere phenotype, and telomere dysfunction. Our results indicate that DEK is required for proper loading of ATRX and H3.3 on telomeres and for telomeric chromatin architecture. We propose that DEK acts as a “gatekeeper” of chromatin, controlling chromatin integrity by restricting broad access to H3.3 by dedicated chaperones. Our results also suggest that telomere stability relies on mechanisms ensuring proper histone supply and routing.
10.1101/gr.173831.114